Evaluation of the Hidden Curriculum in Students’ Character Formation at CLC SMPT Nabawan, Sabah, Malaysia - Ratnawati Syam; Syahrul Syahrul; Kaharuddin Arafah (FKIP - Universitas Riau, 2026)
Character education is a crucial aspect of educational practice, particularly in alternative educational institutions that serve students from diverse social and cultural backgrounds. This study aims to evaluate the implementation of the hidden curriculum in shaping students’ character at CLC SMPT Nabawan, Sabah, Malaysia. The study employed a qualitative approach using the CIPP evaluation model, which consists of context, input, process, and product components. Data were collected through interviews, observations, document analysis, and student questionnaires. The findings indicate that the implementation of the hidden curriculum is supported by a strong contextual foundation, including a character-oriented school vision and mission, a conducive school culture and climate, and positive stakeholder support. The input evaluation shows adequate readiness of school management, teachers, students, and parents, although limitations in facilities and infrastructure remain a challenge. The process evaluation reveals that the hidden curriculum is implemented through intramural learning activities, extracurricular programs, daily habituation, and teacher role modeling. The product evaluation demonstrates that character values such as religiosity, discipline, responsibility, obedience to rules, and social awareness have been well internalized by most students, while responsibility for school facilities still requires improvement. This study concludes that the hidden curriculum is an effective strategy for character development in the context of alternative education and should be strengthened through consistent implementation and systematic evaluation.